KAJIAN KANDUNGAN ZAT GIZI DAN SIFAT SENSORIS LEDOK DARI BEBERAPA JENIS UMBI-UMBIAN - Suarta, I Wayan; Yusa, Ni Made; Suter, I Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2013)
The aim of the study was to determine the nutrition content and sensory properties of ledok which made from various types of tubers. Experiments designed randomized block design which contains of six tubers treatment: yellow sweet cassava, yellow sweet potato varieties papua selulosa, purple sweet potato varieties RIS 03065-03, orange sweet potato varieties sari, white sweet potato varieties sukuh, and white sweet potato varieties cengkuang. Each treatment was repeated three times acquired 18 units of the experiment. The observation of parameters in this study were the moisture content, ash content, fat content, protein content, carbohydrate content, antioxidant capasity, sensory properties including color, aroma, taste, texture and overall acceptance. The data obtained were analyzed by analysis of variance, and if there are significant differences between treatments followed by Duncan Multi Range Test (DMRT). The results showed that, the use of types of tubers have significant effect on the content of fat, protein, carbohydrate, antioxidant capasity and sensory properties of the color, flavor, and texture, and was not significant on the moisture content, ash content and sensory properties of the flavor and overall acceptance. The best ledok was produced from purple sweet potato varieties RIS 03065-03 with the following characteristics: moisture content 73,91% , ash content 0,69%, 3,14% fat content, protein content 10,58%, carbohydrate content 11,67%, antioxidant capasity 91,26% and overall acceptance (rather like)
Keywords: Ledok, sweet potato, sensory properties